Implementation of Scientific Integration in Learning toward the Formation of Student’s Akhlak - Siti Insani Akbari; Irawan Irawan (STAI Hubbulwathan Duri, 2021)
This research aims to determine how the implementation and the effect of scientific integration in learning toward the formation of students' morals. The method used in this research was descriptive using a quantitative approach, for data collection was obtained from questionnaires, interviews, and documentation studies. Meanwhile, the data analysis used the percentage technique for descriptive data and linear regression technique for quantitative data. The results obtained in this study explain that the application of scientific integration is included in the very good category with the acquisition of a percentage of 84%. Second, students' moral formation is in the very good category with a percentage gain of 80.5%. Third, the result of a linear regression calculation shows that the alternative hypothesis (Ha) is accepted and hypothesis Null (H0) is rejected. Science integration contributes 20.1% to the moral formation of students.